Digital innovation, sustainability principles, and multi-sector diversification models of Indonesia’s halal industry: an analysis of sharia economic transformation - Saifuddin, Warto Ahmad; Setiawan, Firman (Universitas Airlangga, 2025)
This study highlights the acceleration of Indonesia’s halal industry, which has undergone a significant transformation from merely fulfilling domestic needs to becoming a strategic pillar of the national economy. This development is driven by the regulatory mandate of the Halal Product Assurance Law and the growing global consumer demand for product integrity. The study aims to comprehensively analyze the fundamental role of digital innovation and the integration of sustainability principles (thayyiban) in promoting product diversification across the food, pharmaceutical, cosmetic, tourism, and Islamic finance sectors during the period of 2019 to 2025. The research employs a descriptive qualitative method using a Systematic Literature Review of reputable journals (Scopus and Sinta) to map strategic trends and identify theoretical gaps. In total, 85 peer-reviewed articles were systematically analyzed, resulting in the development of an integrated conceptual framework that synthesizes digital technology adoption, sustainability ethics, and halal industry diversification. The findings firmly indicate that the adoption of blockchain and Internet of Things (IoT) technologies within the Halal Supply Chain framework represents a fundamental innovation that enhances transparency, operational efficiency, and consumer trust. These findings serve as a crucial foundation for product diversification aligned with the Maqasid Shariah. The main contribution of this study lies in the formulation of an integrated framework that explicitly connects technological innovation, sustainability ethics, and multisector diversification patterns. This framework provides substantial policy recommendations to strengthen the global competitiveness of the national halal ecosystem Keywords: Halal Industry, Digital Innovation, Product Diversification, Halal Supply Chain, Sustainability